Commentary on "A Microfluidic Platform to Design Crosslinked Hyaluronic Acid Nanoparticles (cHANPs) for Enhanced MRI". (1st August 2017) - Russo, Maria; Bevilacqua, Paolo; Netti, Paolo Antonio; Torino, Enza
Strategies to enhance the relaxometric properties of gadolinium (Gd)-based contrast agents (CAs) for magnetic resonance imaging (MRI), without the chemical modification of chelates, have recently had a strong impact on the diagnostic field. We have taken advantage of the interaction between Gadolinium diethylenetriamine penta-acetic acid (Gd-DTPA) and the hydrogel structure of hyaluronic acid to design cross-linked hyaluronic acid nanoparticles down to 35 nm for use in MRI applications. The proposed bioformulations enable the control of the relaxometric properties of CAs, thus boosting the relaxation rate of T1. Our results led us to identify this approach as an adjustable scenario to design intravascularly injectable hydrogel nanoparticles entrapping Gd-DTPA. This approach overcomes the general drawbacks of clinically approved CAs having poor relaxivity and toxic effects.